Solución del Acertijo




1 = (4 + 4) / (4 + 4)
1 = 44 / 44
2 = (4 * 4) / (4 + 4)
2 = 4 / 4 + 4 / 4
3 = ( (4 + 4) + 4) / 4
3 = √( 4 * 4) - 4 / 4
4 = ( (4 - 4) * 4) + 4
4 = 4! - (4 * 4) - 4
5 = ( (4 * 4) + 4) / 4
5 = √( 4 * 4) * 4 / 4
6 = ( (4 + 4) / 4) + 4
7 = (4 + 4) - (4 / 4)
8 = (4 + 4) + (4 - 4)
9 = (4 + 4) + (4 / 4)
10 = (4 + 4) + (4 - √(4))
10 = 4 + √4 + √4 + √4
11 = ( (4 + 4!) / 4) + 4
12 = (4 - (4 / 4)) * 4
13 = (4 / 4) + (4! / √(4))
14 = (4 + 4) + (4 + √(4))
15 = (4 * 4) - (4 / 4)
16 = (4 + 4) + (4 + 4)
17 = (4 * 4) + (4 / 4)
18 = (4 * 4) + (4 - √(4))
19 = (4! - 4) - (4 / 4)
20 = ( (4 / 4) + 4) * 4
20 = 4 * 4 + √4 + √4
21 = (4 / 4) + (4! - 4)
22 = (4 * 4) + (4 + √(4))
23 = ( (4 * 4!) - 4) / 4
24 = (4 + 4) + (4 * 4)
25 = ( (4 / 4) + 4) ^ √(4)
26 = ( (4 + 4) / 4) + 4!
27 = (4 + 4!) - (4 / 4)
28 = ( (4 + 4) * 4) - 4
29 = (4 / 4) + (4 + 4!)
30 = ( (4 + 4) * 4) - √(4)
31 = ( (4 + 4!) / 4) + 4!
32 = (4 * 4) + (4 * 4)
33 = (4 + 4!) + (√(4) / .4)
34 = ( (4 + 4) * 4) + √(4)
35 = ( (4 * 4) - √(4)) / .4
36 = ( (4 + 4) * 4) + 4
37 = ( (√(4) + 4!) / √(4)) + 4!
38 = (4 * 4) + (4! - √(4))
39 = ( (4 + √(4)) / .4) + 4!
40 = ( (4 * 4) + 4) * √(4)
41 = ( (4! - 4) / .4bar) - 4
42 = (4 * 4) + (√(4) + 4!)
43 = ( (4! - 4) / .4bar) - √(4)
44 = (4 * 4) + (4 + 4!)
45 = ( (4 * 4) + 4) / .4bar
46 = ( (4 * 4!) - 4) / √(4)
47 = (√(4) * 4!) - (4 / 4)
48 = ( (4 + 4) + 4) * 4
49 = (4 / 4) + (√(4) * 4!)
50 = ( (4 / 4) + 4!) * √(4)
51 = ( (4! - √(4)) / .4) - 4
52 = ( (4 - √(4)) * 4!) + 4
53* = (4! / .4bar) - (4 / 4)
53* = 44 + 4/.4bar 54 = ( (4 + √(4)) ^ 4) / 4!
55 = (4 / 4) + (4! / .4bar)
56 = ( (4 * 4) - √(4)) * 4
57* = (4 / .4bar) + (√(4) * 4!)
57* = 4! + 4! + 4/.4bar
58 = ( (4 ^ 4) - 4!) / 4
59 = (4! / .4) - (4 / 4)
60 = ( (4 * 4) * 4) - 4
60 = 4 * 4 + 44
61 = (4 / 4) + (4! / .4)
62 = ( (4 * 4) * 4) - √(4)
63 = ( (4 ^ 4) - 4) / 4
64 = (4 + 4) * (4 + 4)
65 = ( (4 ^ 4) + 4) / 4
66 = ( (4 * 4) * 4) + √(4)
66 = 4! / .4 + 4! / 4
67 = ( (4 + 4!) / .4bar) + 4
68 = ( (4 * 4) * 4) + 4
68 = 4 ^ 4 / 4 - 4
69 = ( (√(4) + 4!) / .4) + 4
70 = ( (4 ^ 4) + 4!) / 4
71 = ( (4 + 4!) + .4) / .4
72 = ( (4 * 4) + √(4)) * 4
73* = ( (√(4) * 4!) + √(.4bar)) / √(.4bar)
74 = (4 * 4!) - (4! - √(4))
75 = ( (4 + √(4)) + 4!) / .4
76 = ( (4! - 4) * 4) - 4
77 = ( (4 / .4bar) ^ √(4)) - 4
78 = ( (4! - 4) * 4) - √(4)
79 = ( (4 / .4bar) ^ √(4)) - √(4)
80 = ( (4 * 4) + 4) * 4
81* = (4 - (4 / 4)) ^ 4
82 = ( (4! - 4) * 4) + √(4)
83* = ( (4 / .4bar) ^ √(4)) + √(4)
84 = ( (4! - 4) * 4) + 4
85* = ( (4 / .4bar) ^ √(4)) + 4
86 = ( (4! - √(4)) * 4) - √(4)
87 = (4 * 4!) - (4 / .4bar)
88 = (4 * 4!) - (4 + 4)
89 = ( (√(4) + 4!) / .4) + 4!
90 = (4 * 4!) - (4 + √(4))
91 = (4 * 4!) - (√(4) / .4)
92 = (4! - (4 / 4)) * 4
93* = (4 * 4!) - (√(4) / √(.4bar))
94 = (4 * 4!) - (4 - √(4))
95 = (4 * 4!) - (4 / 4)
96 = (4 * 4) * (4 + √(4))
97 = (4 / 4) + (4 * 4!)
98 = (4 - √(4)) + (4 * 4!)
99* = ( (√(4) * 4!) - 4) / .4bar
100 = ( (4 + 4) + √(4)) ^ √(4)
101 = (4 * 4!) + (√(4) / .4)
102 = (4 + √(4)) + (4 * 4!)
En http://johnvalentine.co.uk/fourfours.php?art=solutions hay más soluciones.